Hubungan Pola Asuh Orang Tua Terhadap KecerdasanEmosi Anak Usia Dini Di TK Melati Ngembat PadasGemolong Sragen Tahun Ajaran 2015/2016 - Wulandari, Diah Ayu; , Drs. Ilham Sunaryo, M Pd (2016)
A permissive parenting is the parenting in which parents give the freedom to seek and determine for the children what they want. Thus it creats a family environment child-centered. This type of parenting the parents tend to spoil or never reprimand or not rebuke the child's behavior even though the child's behavior has gone too far or beyond the limits of reasonableness. This permissive parenting tends to be a spoiled child, self-absorbed, lack of confidence and lack of parental control. Because parents often give freedom or spoil the child, this affects the intelligence of children, especially children's emotions will be hampered or worse. The purpose of this study was to determine the relationship between parenting parents permissive to word emotional intelligence of children in Melati kindergarten at Ngembat Padas Gemolong Sragen Academic Year 2015/2016. This type of research is descriptive kuantitative. The experiment was conducted in kindergarten Melati Ngembat Padas Gemolong. The research sample was 33 children in group A. The technique of sampling used simple random sampling technic. Data analysis used product moment correlation based on the data analysis resulted -0.401 r person with significant correlation. With a significant level of blame of 0.021 < 0.05 (p = 0.021; p < 0.05). Means rxy: rtabel = -0.401: 0, 344, so that rxy<rtabel means -0.401 < 0.344. With a 5% blame level rxy: rtabel = -0.401: 0, 344, so that rxy<rtabel means -0.401 < 0.05. There by significantly by 0.021 < 0.05 (p = 0.021; p < 0.05) or rxy<rtabel = -0.401 < 0.449 < 0.344. It means that Ho is rejected and Ha is received no significant association between permissive parenting parents word emotional intelligence in Melati kindergarten at Ngembat Padas Gemolong Sragen Academic Year 2015/2016.